Ultrasound for Preoperatively Predicting Pathology Grade, Complete Cytoreduction Possibility, and Survival Outcomes of Pseudomyxoma Peritonei - Liang, Lei; Han, Xuedi; Zhou, Nan; Xu, Hongbin; Guo, Jun; Zhang, Qian (Frontiers in Oncology, 2021)
Objectives: This study aimed to investigate the value of using ultrasound (US) preoperatively for predicting pathological classification, complete cytoreduction possibility, and survival rate of patients with pseudomyxoma peritonei (PMP). Methods: We retrospectively studied PMP patients who were scheduled for cytoreductive surgery between May 2009 and October 2019. US examination was performed before surgery. Factors related to high-grade pathology and poor completeness of cytoreduction (CC) score were identified. The Associations between ultrasound characteristics and the survival status were also examined to identify independent predictive factors. Results: PMP patients with clear ascites, abdominal lymph nodes, omental cake, abdominal mass, portal infiltration, and mesenteric involvement visible on US were considered to have high-grade pathology. Various US features were shown to be independent prognostic markers for inadequate cytoreduction in PMP patients. Portal infiltration and mesenteric involvement were significant prognostic factors for lower survival rates (hazard ratio=3.092, 3.932, respectively). A visual nomogram including these factors were constructed to predict survival rates. The consistency index was 0.777, which reflected relatively high accuracy. Conclusions: Preoperative US has the potential to predict pathological grade and resectability of PMP. Portal infiltration and mesenteric involvement were independent predictors of poor clinical outcomes in PMP patients. Furthermore, a simple-to-use nomogram derived from our study data may be a helpful visual tool in clinical practice to predict 1-, 2-, and 3-year survival rates for PMP patients.